Empirically testing the relationship between income distribution, perceived value money and pay satisfaction - Ismail, Azman; Oscar, Dousin; Antonia, Girardi; Ahmad, Zainal Ariffin; Mohd Shariff, Mohd Noor; Majid, Abdul Halim; Abdullah, Muhammad Madi; Ibrahim, Zalina (OmniaScience, 2009)
Compensation management literature highlights that income has three major features: salary, bonus and allowance. If the level and/or amount of income are distributed to employees based on proper rules this may increase pay satisfaction. More importantly, a thorough investigation in this area reveals that the effect of income distribution on pay satisfaction is not consistent if perceived value of money is present in organizations. The nature of this relationship is less emphasized in pay distribution literature. Therefore, this study was conducted to measure the effect of the perceived value of money and income distribution on pay satisfaction using 136 usable questionnaires gathered from employees who have worked in one city based local authority in Sabah, Malaysia (MSLAUTHORITY). Outcomes of hierarchical regression analysis showed that the interaction between perceived value of money and income distribution significantly correlated with pay satisfaction. This result confirms that perceived value of money does act as a moderating variable in the income distribution model of the organizational sample. In addition, discussion and implications of this study are elaborated.